Evaluasi Kinerja Sistem IoT untuk Monitoring pH dan Kontrol Suhu Air pada Akuarium Benih Ikan Clarias gariepinus - Ellys Kumala Pramartaningthyas; Mohamad Hariyadi; Nur Afiyat; Siti Ma’shumah; Didik Sigiono (Infotekmesin, 2026)
The cultivation of Clarias gariepinus requires optimal water quality management, particularly temperature and pH, to support the growth and survival of fry. Conventional manual monitoring methods are limited in terms of continuous observation and rapid response to changes in water quality. This study aimed to develop an Internet of Things (IoT)-based water temperature and pH monitoring and control system capable of real-time and integrated operation. The proposed system was developed using an Arduino UNO, NodeMCU ESP8266, a DS18B20 temperature sensor, a pH sensor, and the Blynk platform, employing a threshold-based automatic control mechanism. Water temperature was regulated using a heating element and a Peltier module. System performance was evaluated through 20 experimental trials conducted in a Clarias gariepinus fry aquarium under varying initial temperature and pH conditions outside the optimal cultivation range to assess the system's monitoring, control, and real-time data transmission capabilities. The experimental results demonstrated that the proposed system successfully maintained the water temperature at 26 °C and the pH at 6, which are within the recommended aquaculture standards. The temperature and pH sensors achieved accuracies of ±0.4% and ±0.5%, respectively, while the average communication delay was 13.59 ms, indicating fast and stable data transmission. Compared with conventional manual monitoring, the proposed IoT-based system provides continuous real-time monitoring, faster response, and automatic environmental control, thereby improving the efficiency and reliability of water quality management for Clarias gariepinus fry culture.